Among the islands - Flannery, Tim F. (Tim Fridtjof), 1956- (Atlantic Monthly Press ; Distributed by Publishers Group West, 2012)
A scientist credited with discovering more species than Darwin recounts the first major trips of his career, several expeditions to often remote Pacific islands where he found amazing animals, harsh weather, strange local taboos, and dense jungle.